Short biographical account of Joseph Mary Plunkett [by Grace Plunkett?], - Plunkett, Grace Gifford, 1888-1955, artist.
The biography ends with a poem by Joseph Mary Plunkett that begins with: "His songs were a little phrase / Of eternal song,...".